2013
DOI: 10.1007/s11434-013-5996-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the consistency of atmospheric CO2 retrievals from different space-based sensors: Intercomparison and spatiotemporal analysis

Abstract: In recent years, global warming caused by emission of CO 2 has attracted considerable attention from the public. Although the measurements from AIRS, GOSAT, SCIAMACHY and IASI have been frequently used to derive atmospheric CO 2 concentration, comprehensive quantification of the differences among these CO 2 products is still not fully investigated yet. In this paper, a series of strategies have been proposed to allow the CO 2 products from different instruments to be physically inter-comparable. Based on this,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
(44 reference statements)
3
13
0
Order By: Relevance
“…Although the data points from ACOS are slightly wider than those from BESD, both ACOS and BESD show poor global coverage. These results agree with those presented in the study conducted by Wang et al [11].…”
Section: Global Spatial Distribution Of Xco 2 For Fused Acos and Besdsupporting
confidence: 94%
See 3 more Smart Citations
“…Although the data points from ACOS are slightly wider than those from BESD, both ACOS and BESD show poor global coverage. These results agree with those presented in the study conducted by Wang et al [11].…”
Section: Global Spatial Distribution Of Xco 2 For Fused Acos and Besdsupporting
confidence: 94%
“…Bai et al [35] stated that significant seasonal variations of CO 2 in the Northern Hemisphere were closely related to human activities and green vegetation. Wang et al [11] also found that seasonal cycles exist in the retrieved XCO 2 concentrations from satellites in the Northern Hemisphere and that there are no significant seasonal variations in the Southern Hemisphere. From Figure 4, we can also see that there is no noticeable seasonal variation in the Southern Hemisphere, particularly for Australia and the southern part of South America.…”
Section: Monthly Variability For Predicting the Fused Datamentioning
confidence: 98%
See 2 more Smart Citations
“…Due to different samplings method, for example, different satellites, different overpass, and different filtering strategies, etc., it is necessary to unify these differences into the same level before combining ACOS and BESD XCO 2 products into a fused data [12,14].…”
Section: Methodsmentioning
confidence: 99%